Early Effects of Perfluorohexyloctane Ophthalmic Solution on Patient-Reported Outcomes in Dry Eye Disease: A Prospective, Open-Label, Multicenter Study - Jason Bacharach; Shane R. Kannarr; Anthony Verachtert; Preeya K. Gupta; Moataz Razeen; Megan E. Cavet; Jason L. Vittitow; Jacob Lang; Thomas M. Chester; Jillian F. Ziemanski; Darrell E. White (Ophthalmology and Therapy)
Abstract Introduction Perfluorohexyloctane ophthalmic solution (PFHO) is indicated for the treatment of signs and symptoms of dry eye disease (DED) and targets excessive tear evaporation. This study evaluated patient-reported outcomes early in treatment with PFHO. Methods This prospective, multicenter, open-label, phase 4 study enrolled adults with a history of DED for ≥ 6 months. PFHO was instilled in both eyes four times daily for 14 days. Patients completed early outcome surveys during four clinic visits (day 1 [pretreatment; 5 and 60 min post-PFHO instillation] and days 3, 7, and 14). Symptom severity, symptom frequency, and treatment satisfaction were rated on visual analog scales (range 0–100). The primary endpoint was mean change from baseline in overall DED symptom severity at day 7. Secondary endpoints included change in severity of individual DED symptoms (eye dryness, blurred vision, eye irritation, light sensitivity, eye tiredness, burning/stinging, eye itching, eye pain); change in frequency (measured as percentage of time experienced) of the most bothersome symptom, awareness of dry eye symptoms, and fluctuation in quality of vision; and treatment satisfaction. Results Ninety-nine patients enrolled (85.9% female; age range 35–81 years). The primary endpoint was met: mean (SD) overall symptom severity decreased significantly from 72.1 (17.0) at baseline to 27.8 (22.3) at day 7 (mean change, − 44.5; P < 0.0001). Mean (SD) percentage of time experiencing the most bothersome symptom decreased from 77.9% at baseline to 34.7% at day 14 (P < 0.0001). Significant reductions in severity and frequency also were observed for all symptoms at all postbaseline assessments (P < 0.0001). Median ratings of treatment satisfaction were 83.0 at day 3, 86.0 at day 7, and 90.0 at day 14. Conclusion Early in the course of treatment with PFHO, patients with DED experienced significant reductions in dry eye symptom frequency and severity. Treatment satisfaction with PFHO was high. Trial Registration ClinicalTrials.gov identifier NCT06309953.